Judicial Review Di Mahkamah Agung - Ratna Rumingsih (Jatiswara, 2011)
In Indonesia, the legal arrangements concerning judicial review into a matter that seriously debated since the founding fathers talked about the constitution that will apply when Indonesia has been independent. Whether to include or not judicial review in its constitution. The Supreme Court has the authority to test the material only to the laws and regulations under the legislation, Article 31 of Law No. 14 of 1985 on the Supreme Court and Article 26 of Law No. 14 of 1970 Law No. jo. 31 of 1999 on the provision on the Fundamentals of Judicial Power. The right test is materially against the law is an authority given to the judiciary to examine whether a regulation does not conflict with higher regulations. This authority is given to the Supreme Court so that regulations made by the legislature and executive can be tested whether or not in accordance with the rules is higher. The authority of the Supreme Court in a right to test the material against the legislation is limited to the regulations under the statute.